2013
DOI: 10.1007/s00787-013-0488-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of childhood conduct problem trajectories in early adulthood: findings from the ALSPAC study

Abstract: Although conduct problems in childhood are stably associated with problem outcomes, not every child who presents with conduct problems is at risk. This study extends previous studies by testing whether childhood conduct problem trajectories are predictive of a wide range of other health and behavior problems in early adulthood using a general population sample. Based on 7,218 individuals from the Avon longitudinal study of parents and children, a three-step approach was used to model childhood conduct problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 43 publications
7
70
2
2
Order By: Relevance
“…Kretschmer et al [24] Mother-reported conduct problems, using the "conduct problem" subscale of the SDQ. The sum score was dichotomised using the standard threshold of scores of 4 or more, yielding 6 binary indicators for the latent growth classes Depression and anxiety measured using the clinical interview schedule-revised (CIS-R), a self-administered computerised interview that derives diagnoses based on ICD-10 criteria for depression and anxiety disorder (GAD, panic, phobia, social anxiety) Risky sexual behaviour: respondents were asked how many sexual partners they had had in the last year and were assigned a score of one if they reported three or more different partners Xie et al [22] Interpersonal competence scaleteacher administered (which assesses aggression, popularity, and academic competence)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kretschmer et al [24] Mother-reported conduct problems, using the "conduct problem" subscale of the SDQ. The sum score was dichotomised using the standard threshold of scores of 4 or more, yielding 6 binary indicators for the latent growth classes Depression and anxiety measured using the clinical interview schedule-revised (CIS-R), a self-administered computerised interview that derives diagnoses based on ICD-10 criteria for depression and anxiety disorder (GAD, panic, phobia, social anxiety) Risky sexual behaviour: respondents were asked how many sexual partners they had had in the last year and were assigned a score of one if they reported three or more different partners Xie et al [22] Interpersonal competence scaleteacher administered (which assesses aggression, popularity, and academic competence)…”
Section: Resultsmentioning
confidence: 99%
“…Although indistinguishable from EOP in terms of baseline symptoms of conduct problems, CL individuals did not show significantly higher risk of poor outcomes on most of the measures considered in this study. Similarly, Kretschmer et al [24] found that EOP individuals were at higher risk compared to low conduct problems individuals on a number of outcomes including smoking and substance use, criminal and risky sexual behaviour, gambling, and mental health at age 18. Higher rates of risky sexual behaviour and substance use were observed in AO individuals.…”
Section: Introductionmentioning
confidence: 96%
“…Maternal reports of child conduct problems were collected when children were aged 4, 7, 8, 10, 12 and 13 years using the Strengths and Difficulties Questionnaire (SDQ), a widely used screening instrument with well‐established reliability and validity (Goodman, ). Using cases with 4–6 SDQ scores between ages 4–13, four trajectories of conduct problems were previously identified in growth mixture models (Barker & Maughan, ; Heron et al., ; Kretschmer et al., ): a low‐risk class, maintaining low levels of conduct problems throughout the study; a childhood‐limited class, initiating conduct problems in early childhood but desisting to low levels by age 13; an adolescence‐onset class, starting at low levels of conduct problems but increasing by age 13, and an early‐onset‐persistent group, initiating conduct problems early in childhood and persisting into early teens.…”
Section: Methodsmentioning
confidence: 99%
“…29 This emphasizes the importance of extending surveillance to at least school age for children after NAS as failure to diagnose and treat these conditions in a timely manner may lead to school difficulties, poor adult productivity, and psychological function. 30 Of great concern is the significantly increased risk of hospitalization caused by maltreatment or trauma (up to 36-fold for unspecified causes of maltreatment) that occurred significantly earlier (mostly during the first 4 months) than those without NAS (admissions closer to their first birthday). This may reflect a drop-off in support provided to substance-affected parents and caregivers in the first few weeks to months after birth but which may be difficult to maintain due to pressure on resources.…”
Section: Figurementioning
confidence: 99%